Oropharyngeal adverse drug reactions: knowledge, attitudes, and practice (KAP) among Italian healthcare professionals and students - La Mantia, Gaetano; Marcon, Giulia; Coppini, Martina; Buttacavoli, Fortunato; Panzarella, Vera; Colella, Giuseppe; Capuano, Annalisa; Sportiello, Liberata; Parrinello, Gaspare; Morreale, Ilaria; Oteri, Giacomo; Bellavia, Giuseppe; et al. (Frontiers in Public Health, 2025)
IntroductionPharmacovigilance plays a vital role in ensuring drug safety and protecting public health. Oropharyngeal adverse drug reactions (O-ADRs) are found to be under-reported, especially by oral health professionals, limiting the identification and management of these events.AimsThis study aimed to evaluate the knowledge, attitudes, and practices (KAP) of healthcare professionals and students regarding O-ADRs and to assess their specific expertise by a self-e-learning test.Materials and methodsA cross-sectional survey was conducted using a KAP questionnaire between April 2023 and April 2024, involving 943 participants, including physicians, dentists, dental hygienists, and students. Additionally, three sets of self-e-learning tests on O-ADRs were administered. The study employed descriptive statistics, Kruskal-Wallis tests, and logistic regression to analyze factors affecting KAP and reporting behaviors.ResultsSignificant gaps in KAP were identified. Only 26.5% of participants demonstrated frequent best practices for reporting O-ADRs, with dentists and dental hygienists showing lower reporting rates (13.8% and 9.3%, respectively) compared to physicians (18.8%). The results of logistic regression analyses showed that practical knowledge was significantly associated with work experience (OR = 2.15, p = 0.026). Students exhibited the lowest levels of practical knowledge and reporting proficiency, with only 17.6% demonstrating competence. The self-e-learning test highlighted knowledge deficits: only 22.9% of participants correctly identified O-ADR associated with antiseptic mouth rinses, additional 30.2% recognized those linked to antimicrobial drugs.ConclusionsThis study highlights the need for targeted educational interventions to address gaps in O-ADR knowledge and practice. Tailored training, user-friendly digital tools, and a strong pharmacovigilance culture are crucial for improving reporting rates and ensuring patient safety.